2019
DOI: 10.1002/eet.1867
|View full text |Cite
|
Sign up to set email alerts
|

Actor relations in climate policymaking: Governing decarbonisation in a corporatist green state

Abstract: This article focuses on the role of actor relations in advancing climate policymaking and argues that attempts to understand decisions to decarbonise in a green state should explore the institutional conditions for policymaking. The article explores the climate policy model in Sweden in terms of the societal actors included in the policy process, the nature of this inclusion, and its relevance for the prospects of decarbonisation. It uses three perspectives in the analysis: corporatism, sustainable transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 39 publications
(47 reference statements)
0
19
0
1
Order By: Relevance
“…MLG's conceptual vocabulary, however, of flattening hierarchies, power sharing, and complementary competencies arguably obscures the nuances of power relations. Though more recent scholarship increasingly asks which levels or actors are most influential in tipping the scales of policy making, it mostly probes these power asymmetries in European and Western liberal democratic polities (Alcantara and Morden 2019; Kronsell, Khan, and Hildingsson 2019; Ongaro et al . 2010)—raising questions on how power differentials within MLG arrangements present themselves in nondemocratic, non‐Western and/or Global South countries (but see Di Gregorio et al .…”
Section: Literature Review: Wither the Politics?mentioning
confidence: 99%
“…MLG's conceptual vocabulary, however, of flattening hierarchies, power sharing, and complementary competencies arguably obscures the nuances of power relations. Though more recent scholarship increasingly asks which levels or actors are most influential in tipping the scales of policy making, it mostly probes these power asymmetries in European and Western liberal democratic polities (Alcantara and Morden 2019; Kronsell, Khan, and Hildingsson 2019; Ongaro et al . 2010)—raising questions on how power differentials within MLG arrangements present themselves in nondemocratic, non‐Western and/or Global South countries (but see Di Gregorio et al .…”
Section: Literature Review: Wither the Politics?mentioning
confidence: 99%
“…Relating to theories developed by Levin et al [17], Hildingsson and Khan [70] found support for a gradually more progressive approach to policy change in the case of the Swedish energy transition. Taking a wider governance perspective, and with Sweden as an example, Hildingsson, Kronsell and Khan [71] analysed the role of the state in governing the decarbonisation of ENRIs, while Kronsell, Khan and Hildingsson [72] studied actor relations in climate policy making. They find that the tension between the state's economic imperative and ecological concerns in greening industry are shown to persist.…”
Section: Main Thematic Contributionmentioning
confidence: 99%
“…One major example is the urgent need for global transformation to keep the earth system under the 1.5 • C scenario. The decarbonization of energy systems is promoted as a solution but is still widely resisted by different actors [108,109]. Nevertheless, the international agreement on the reduction of greenhouse gas emissions, the "Kyoto Protocol", adopted in 1997 and entering into force in 2005, has not yet produced the desired cut-off effects as some nations claim their right to emit CO 2 without restriction, thus creating tensions with those who try to abide by the protocol.…”
Section: Global Scalementioning
confidence: 99%